Amelioration of alcohol-induced acute liver injury in C57BL/6 mice by a mixture of TCM phytochemicals and probiotics with antioxidative and anti-inflammatory effects - Li, Zhiguo; Fang, Xuexun; Hu, Xin; Li, Congcong; Wan, Youzhong; Yu, Dahai (Frontiers in Nutrition, 2023)
Background: There are many causes of acute liver injury (ALI), such as alcohol, drugs, infection and toxic materials, which have caused major health problems around the world. Among these causes, alcohol consumption induced liver injury is a common alcoholic liver disease, which can further lead to liver failure even liver cancer. A number of traditional Chinese medicine (TCM) and TCM derived compounds have been used in treating the liver-associated diseases and combination use of probiotics with TCM phytochemicals has attracted interests for enhanced biological effects. Methods: This study investigated the hepato-protective effect of TCM-probiotics complex (TCMPC) and its underlying mechanism for the treatment of ALI in mice. The TCMPC is composed of TCM phytochemicals puerarin, curcumin, ginsenosides and 5 lactobacteria strains. We first established a mouse model of alcohol-induced ALI, then the therapeutic effects of TCMPC on alcohol-induced ALI were monitored. A series of measurements have been performed on anti-oxidation, anti-inflammation and lipid metabolism regulation. Results: The results showed that TCMPC can reduce the level of liver injury biomarkers and regulate oxidative stress. Histopathological results indicated that TCMPC could ameliorate ALI in mice. In addition, it can also significantly reduce the production of inflammatory cytokines caused by ALI. Conclusion: Our research has proved the therapeutic effect of TCMPC on alcohol-induced ALI. The potential mechanism of hepatoprotective effects of TCMPC may be related to its anti-oxidative and anti-inflammatory effects. Our research might provide a new way for liver disease treatment.